HUBUNGAN SELF CONFIDENCE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Fauziah, Rima; Maya, Rippi; Fitrianna, Aflich Yusnita (IKIP Siliwangi, 2018)
This research was conducted to analyze the relationship between self confidence with the ability of mathematical problem solving of IX grade junior high school students. Research method is correlation analysis. The subject of this study consisted of 35 students of student in grade IX junior high school in Cimahi. Sampling technique using random technique. The test were done by giving about problem solving skills in the form of essay 5 items and self confidence questionnaire with Likert scale. The data analysis steps used were normality, correlation test, determine the coefficient of determination or coefficient determinant to see contribution or influence of variable self confidence to variable the ability of mathematical problem solving and continued with significance test (t test). Based on the result of research, it can be conclude that there is a significant relationship between self confidence in the ability of solving mathematical problems of junior high school students.Keywords: the ability of mathematical problem solving, self confidence, junior high school students.